Spectrum of heart diseases on Echocardiography in a Rural tertiary care Medical college hospital in Bangladesh - Islam, Md Saiful; Sakib, Md Annaz Mus; Talukder, Ranjan; Yusuf, Sheikh Mohammed Taslim (KYAMC Journal, 2013)
Background: Echocardiography is a non-invasive, on-injurious, relatively cheap and useful imaging technique for the evaluation of cardiac diseases. The procedure has reliable levels of accuracy. Echocardiography commenced at the Cardiology Department of Khawja Yunus Ali Medical College Hospital,Enayetpur Sirajgonj,Bangladesh since 2004.The aim of this study is to report our experience with the procedure, and to define the clinical cases seen in our setting. Methods: This is a retrospective analysis of a prospectively collected data. Echocardiography was performed using Aloka Prosound-SSD 5500 SV echocardiograph equipped with 2.5-5.0 MHz transducer. Results: During the period of 6 months under review (July 2011-December 2011), 1883 procedures were performed. Those reports were reviewed for demographic parameter, indications for the procedure and the main echocardiographic diagnoses. The mean age of the 1883 individuals studied was 50 +/- 18.67 years (10-90). There were 1221 men and 662 women. Four hundred ninety eight(498) (26.45%) had Ischemic Heart Disease, 229(12.16%) subjects were Hypertensive Heart disease,160 subjects (8.5%) had rheumatic heart disease while 62,(3.3%) had cardiomyopathy. Pericardial diseases, corpulmonale, congenital heart diseases, were present in 36(1.92%), 35 (1.85%), 88(4.67%), respectively. Seven hundred and Seventy Five (41.1%) subjects had normal study. Conclusion: Ischemic heart disease was found to be the most prevalent cardiac condition in this study. The relatively frequent diagnoses of Hypertensive heart Disease, valvular heart disease, cardiomyopathies and pericardial diseases reflect the impact of infections on the cardiovascular health of adult Bangladeshis. We suggest that prevention and treatment of cardiac diseases in our setting should among other things focus on life style modification, Ceasation of smoking,regular exercise, blood pressure and blood glucose control and early treatment of infections causing heart diseases. DOI: http://dx.doi.org/10.3329/kyamcj.v3i1.13657 KYAMC Journal Vol. 3, No.-1, June 2012 p.223-224